Character Education Values In Ghutong Rojhung Tradition at The Larangan Luar Village, Dusun Bertah - Jannah, Fira Datul; Effendy, Moh. Hafid (UNIVERSITAS PAKUAN, 2025)
This paper seeks to illuminate the embedded values of character education manifest within the ghutong rojhung practices conducted during communal events in Larangan Luar Village, Bertah Hamlet. Employing a qualitative framework with an ethnography of communication design, data were amassed through immersive observation, dialogical interviews, and meticulous documentation. The analytic journey encompassed stages of data distillation, pattern visualization, and inferential synthesis. The findings unveil that despite the tides of modernization, the ritual of ghutong rojhung persists vibrantly among the populace. Communal undertakings such as prayer gatherings (tahlilan), collaborative construction of water channels, collective building projects, and various forms of mutual assistance continue to thrive, preserving the spirit of ghutong rojhung in Larangan Luar, Bertah Hamlet.